(2x+4)(5x-6)=

Simple and best practice solution for (2x+4)(5x-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+4)(5x-6)= equation:


Simplifying
(2x + 4)(5x + -6) = 0

Reorder the terms:
(4 + 2x)(5x + -6) = 0

Reorder the terms:
(4 + 2x)(-6 + 5x) = 0

Multiply (4 + 2x) * (-6 + 5x)
(4(-6 + 5x) + 2x * (-6 + 5x)) = 0
((-6 * 4 + 5x * 4) + 2x * (-6 + 5x)) = 0
((-24 + 20x) + 2x * (-6 + 5x)) = 0
(-24 + 20x + (-6 * 2x + 5x * 2x)) = 0
(-24 + 20x + (-12x + 10x2)) = 0

Combine like terms: 20x + -12x = 8x
(-24 + 8x + 10x2) = 0

Solving
-24 + 8x + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-12 + 4x + 5x2) = 0

Factor a trinomial.
2((-2 + -1x)(6 + -5x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2

Solution

x = {-2, 1.2}

See similar equations:

| 29=5-3h | | 4*-3+7= | | 4*-3=7 | | 2(5z-1)-5(z+2)=2(z+1) | | 5+2n-4=5n+2-2n | | -14=-7t | | 10p-11=-2p+7 | | 3.5q-2.7-3.9q=-1.4q-5.2 | | 2(3x-4)-(2x-4)= | | 45-23=x | | 25x-30x-16=0 | | -16-9-2= | | 4(x+15)=17x | | -4y+8=5y+9 | | -4(-2+5)= | | 5t^2+14x+3=0 | | 6y+8y=98 | | 15+2(9-6)+9= | | 5x-y+15=0 | | 15+2(9-6)-9= | | x-15=-4 | | -18+12+-6= | | -9(3b+1)+(28b-9)=0 | | (-18)(12)(-6)= | | 5p-6(p-5)+5(q-5)= | | 3(-6)(4)(-2)= | | (6u^3)(-5u^7v^6)= | | 3(-6)(4)(-2)=(-18)(12)(-6) | | 18=6x | | 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 |

Equations solver categories